Recognizing diversity in blennioid fish nomenclature (Teleostei: Blennioidei) - Hastings, Philip A.; Springer, Victor G. (Zootaxa, 2009)
Species inventories for macroecology, biogeography and conservation biology rely upon accurate lists of valid species. In order to provide a more uniform taxonomic treatment for blennioid fishes, we evaluated the taxonomic status of 21 species with currently recognized subspecies. In six cases we found no compelling evidence for recognizing these nominal forms as distinct species. However, in 15 cases, evidence exists for elevating 17 subspecies to full species status based on currently used criteria for delimiting fish species. This evidence includes the existence of significant phenotypic and/or genetic differences supporting the hypothesis that they are on distinct evolutionary pathways in accordance with a phylogenetic species concept. Known distributions of affected species are modified accordingly. Most of these elevated species are separated from their closest relatives by well-known biogeographic barriers.